The River God Cult and the Reshaping of Political Authority—Reading Inscriptions from the Hezhong Area in Tang China - Jiang, Aihua (Religions, 2024)
The River God cult held a significant place in state rituals in imperial China. While scholars have primarily focused on the evolution of the River God sacrificial system, with its interplay of the official granting of noble titles and popular beliefs, this paper offers a further examination of the River God cult. By reading the “Stele of the (Shrine) Temple for the River God honored as the Duke of Numinous Source” (hedushen lingyuangong cimiao bei 河瀆神靈源公祠廟碑), created in the Tang Dynasty, this study explores the interactive relationship between the River God cult and state power in the Hezhong 河中area during that time period. We contend that the traditional River God cult and the participation of both officials and civilians in common rituals throughout past dynasties not only created a concentration of historical memories and reverent emotions but also established a strong social foundation for belief in the River God within the Hezhong region. This cult attracted both state endorsement and popular support. Thus, Guo Ziyi 郭子儀 (697–781), a famous military general in the Tang Dynasty, sought to renovate a temple and erect a monument for the River God. This monument was to serve as a cultural symbol that would strengthen the connection between the state and the local community, and hence ease the social tensions in the Hezhong area after the An Lushan Rebellion. In sum, such a construction would enhance the psychological and cultural identity of the people with both the mandate of heaven and the Tang imperial authority.